RIPK1 polymorphisms and expression levels: impact on genetic susceptibility and clinical outcome of epithelial ovarian cancer - Xuedong Wang; Kui Deng; Jing Tao; Juan Zou; Yiting Du; Li Dai (Cancer Cell International, 2023)
Abstract Background The aim of this study was to explore the associations of RIPK1 polymorphisms, plasma levels and mRNA expression with susceptibility to epithelial ovarian cancer (EOC) and clinical outcome. Methods Three hundred and nineteen EOC patients included in a 60-month follow-up program and 376 controls were enrolled. Two tag SNPs (rs6907943 and rs9392453) of RIPK1 were genotyped using polymerase chain reaction (PCR)-restriction fragment length polymorphism (RFLP) method. Plasma levels of RIPK1 and RIPK1 mRNA expression in white blood cells were determined by ELISA and qPCR, respectively. Results For rs9392453, significantly increased EOC risk was found to be associated with C allele (P = 0.002, OR = 1.49, 95%CI  1.15–1.92), and with CT/CC genotypes in the dominant genetic model (P = 0.006, OR = 1.54, 95%CI  1.12–2.08). CC haplotype (rs6907943-rs9392453) was associated with increased EOC susceptibility. CC genotype of rs6907943 and CT/CC genotypes of rs9392453 were associated with early onset (age ≤ 50 years) of EOC (OR = 2.5, 95%CI  1.03–5.88, and OR = 1.64, 95%CI  1.04–2.63, respectively). AC genotype of rs6907943 was associated with better overall survival of EOC patients in the over-dominant genetic model (P = 0.035, HR = 0.41, 95%CI  0.18–0.94). Multivariate survival analysis identified the AC genotype of rs6907943 as an independent protective factor for survival of early onset patients (P = 0.044, HR = 0.12, 95%CI  0.02–0.95). Compared to controls, significantly increased plasma levels of RIPK1 and reduced RIPK1 mRNA expression were observed in patients. Conclusions Our results suggest that tag SNPs of RIPK1, increased plasma levels of RIPK1 protein and reduced RIPK1 mRNA expression in white blood cells, may influence the susceptibility to EOC. SNP rs6907943 may be a useful marker to distinguish EOC patients with high risk of death.